Commodity risk assessment of bonsai plants from China consisting of Pinus parviflora grafted on Pinus thunbergii. (8th February 2022) - ,; Bragard, Claude; Baptista, Paula; Chatzivassiliou, Elisavet; Di Serio, Francesco; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; et al.
Abstract: The European Commission requested the EFSA Panel on Plant Health to prepare and deliver a scientific opinion on the risk posed by bonsai plants from China consisting of Pinus parviflora grafted on Pinus thunbergii taking into account the available scientific information, including the technical information provided by China. All pests associated with P. parviflora and/or P. thunbergii were evaluated against specific criteria for their relevance for this Scientific Opinion. Forty‐three pests that fulfilled all relevant criteria were selected for further evaluation. For 24 pests that are not quarantine in the EU, the risk mitigation measures described in the technical dossier from China were evaluated taking into account the possible limiting factors. For these pests, an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. While the estimated degree of pest freedom varied among pests, Setoptus parviflorae was the pest most frequently expected on the commodity. The Expert Knowledge Elicitation indicated, with 95% certainty, that 9, 114 or more bonsai plants per 10, 000 will be free from Setoptus parviflorae . For 19 pests that are quarantine in the EU, the implementation of specific measures defined in point 30 and 31 of Annex VII of Commission Implementing Regulation (EU) 2019/2072 was evaluated. The requirements of point 31 are met, whereas those of point 30 are not completely fulfilled.